Measuring Service Delivery Orientation For Doctor and patients Perspective Experimental Study in Numan General Hospital - عبد الوهاب, نادية لطفي (Journal of Economics and Administrative Sciences, 2015)
This research aims to Measurement provide the service from Two perspectives The first perspective Service Provider (doctors) and the second recipient of the service (patients) in Numan General Hospital, and represented the research problem in perceptions of medical staff in the hospital assigned to them responsibility by providing superior services satisfy customers, and how they maintained ready to assist customers and provide services that exceed their perceptions of these services through the use of the developer scale by (Frimpong and Wilson, 2012), includes orientation to provide the service scale four dimensions (Internal cooperative behaviors, service Competence, Service Responsiveness and Enhanced service) and includes doctors perspective Scale (22) items and scale customers perspective (patients) (16) items, and research involved doctors and by 54 doctors from various disciplines and (209) of customers (patients) Recumbent to the hospital, were verified validity and reliability of the scale, and used several methods Statistical to get the results such as ((Factor Analysis) and test (Mann - Whitney) of the differences moral using statistical software (SPSS) version twenty one, and research found several conclusions including the existence of significant differences for more than a dimension of orientation scale to provide the service (Internal cooperative behaviors, service Competence, Enhanced service), suggesting that the customer perspective to go to provide the service Alien from doctors for the same dimensional perspective, this confirms that the perceptions of customer service did not match with what is offered in the hospital, and recommended Find the need to address the opinions of the customers (patients) in the evaluation of the quality of services being provided give clearer indications of the level of the provider of services, since it is not clear dramatically this level of recognition without the opinion of service recipients and their conviction that these services had met the needs and perceptions about the service you wish to receive it